Fabrication of Iron-Containing Biochar by One-Step Ball Milling for Cr(VI) and Tetracycline Removal from Wastewater - Jiang, Fei (Langmuir : the ACS journal of surfaces and colloids, 2023)
Simple ball milling technology can simultaneously improve the adsorption performance of adsorbents for heavy metals and organic pollutants and has attracted increasing attention. Iron-modified biochar (FeMBC) was prepared by one-step ball milling, and the characterization results proved that FeCl3 was successfully loaded on biochar. The removal rates of Cr(VI) and tetracycline hydrochloride (TC) by Fe@MBC were increased by 88.27% and 82.64% compared with BC. The average pore size, oxygen-containing functional groups and graphitization degree of Fe@MBC are higher than those of BC, which is more conducive to promoting adsorption. The adsorption isotherms show that the adsorption of Cr(VI) and TC on the Fe@MBC surface conforms to the Langmuir type of single-layer adsorption and the Freundlich model of multilayer adsorption, respectively. The maximum adsorption capacities of Cr(VI) and TC are 25.46 and 66.91 mg·g-1, respectively. Kinetic experiments show that the adsorption process is more consistent with the pseudo-second-order model of chemical adsorption. The adsorption process of Cr(VI) and TC on the Fe@MBC surface is a spontaneous endothermic process that becomes more obvious as the temperature increases. The increase in solution pH has a significant impact on the removal rate of Fe@MBC. When the pH value increased from 3 to 11, the adsorption rates decreased by 53.74% and 17.16%, respectively. The presence of PO43-, CO32-, K+, and Cu2+ significantly affects the adsorption of TC by Fe@MBC, and PO43- and CO32- also affect the adsorption of Cr(VI). Mechanistic studies show that ion exchange, electrostatic interaction, pore filling, and hydrogen bonding contribute to the removal of Cr(VI) and TC by Fe@MBC. The removal mechanism of Cr(VI) also involves complexation and redox reactions, and the removal mechanism of TC involves π-π bonds and van der Waals forces. The results show that Fe@MBC is a green and efficient adsorbent